Performance Monitoring of Anaerobic Digestion at Various Organic Loading Rates of Commercial Malaysian Food Waste - Zainal, Afifi; Harun, Razif; Idrus, Syazwani (Frontiers in Bioengineering and Biotechnology, 2022)
Application of anaerobic digestion (AD) has been common in treating palm oil mill effluent in Malaysia, however utilizing the AD in treating the organic fraction of municipal solid waste (OFMSW), especially food waste, is still scarce. This study aims to characterize the Commercial Malaysian Food Waste (CMFW) and determine its potential as sustainable bioenergy feedstock through biogas production. The sample was digested via Biomethane Potential (BMP) Test with the variation of organic loading rates (OLR), ranging from 0.38 to 3.83 gCOD/L.day, under mesophilic conditions. The digestion process was further evaluated in continuous operation using a 6L continuous stirred tank reactor (CSTR). The kinetics properties of the process were also determined. It was found that the CMFW had a significant amount of chemical oxygen demand of 230 g/L and acidic (pH 4.5) with Carbon to Nitrogen (C/N) ratio at 121:1. A maximum methane composition of 81% was obtained at 1.92 gCOD/L in the BMP test with Specific Methane Production (SMP) at 0.952 L.CH4/L.COD fed. The biogas production was well fitted with the modified Gompertz model with R2 at 0.9983, and the maximum biogas potential production rate, Rm 0.1573 L/day. Whereas in the CSTR operation, a maximum methane composition of 85% was produced at OLR 6 gCOD/L.day with the SMP of 1.13 L.CH4/L.COD fed. The CSTR system was in high stability as the pH was maintained in a range of 6.6 – 6.7, with an alkalinity ratio of 0.28. This study indicates the CMFW is a sustainable feedstock for biogas production in Malaysia. Towards a circular economy approach, the authorities shall introduce commercial scale CMFW AD as part of managing municipal solid waste issues in Malaysia.